2023
DOI: 10.3390/ijms241311203
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Copper Sulfate and Trichlorfon Exerts Stronger Toxicity on the Liver of Zebrafish

Abstract: In aquaculture, copper sulphate and trichlorfon are commonly used as disinfectants and insecticide, sometimes in combination. However, improper use can result in biotoxicity and increased ecological risks. The liver plays a crucial role in detoxification, lipid metabolism, nutrient storage, and immune function in fish. Selecting the liver as the main target organ for research helps to gain an in-depth understanding of various aspects of fish physiology, health, and adaptability. In the present study, zebrafish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This approach has become particularly relevant given the mounting environmental concerns and economic constraints confronting healthcare systems globally. Prior studies have focused on the pharmacodynamics and pharmacokinetics of antiviral agents, often overlooking the extensive ecological and economic implications linked to their widespread application [ 8 , 23 , 24 ]. Through the eco-pharmaco-economic analysis, nuanced distinctions among the leading antiviral chemicals were revealed.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has become particularly relevant given the mounting environmental concerns and economic constraints confronting healthcare systems globally. Prior studies have focused on the pharmacodynamics and pharmacokinetics of antiviral agents, often overlooking the extensive ecological and economic implications linked to their widespread application [ 8 , 23 , 24 ]. Through the eco-pharmaco-economic analysis, nuanced distinctions among the leading antiviral chemicals were revealed.…”
Section: Resultsmentioning
confidence: 99%
“…After acute hypoxic stress, a study of the liver structure showed that the amount of mitochondria in hepatocytes of Trachinotus ovatus decreased, whereas intracellular ROS levels increased, and the antioxidant system was enhanced to attenuate oxidative damage [53]. In another study, transmission electron microscopy results also revealed that significant amounts of vacuolated mitochondria were observed in zebrafish hepatocytes under Cu exposure [54].…”
Section: Mitochondria Are Target Organellesmentioning
confidence: 97%
“…This approach has become particularly relevant given the mounting environmental concerns and economic constraints confronting healthcare systems globally. Prior studies have focused on the pharmacodynamics and pharmacokinetics of antiviral agents, often overlooking the extensive ecological and economic implications linked to their widespread application [8,23,24]. Through eco-pharmaco-economic analysis, nuanced distinctions among the leading antiviral chemicals were revealed.…”
Section: Figurementioning
confidence: 99%